Dual-Antiplatelet Therapy May Not Be Associated With an Increased Risk of In-hospital Bleeding in Patients With Moderate or Severe Ischemic Stroke - Khazaal, Ossama; Rothstein, Aaron; Husain, Muhammad R.; Broderick, Matthew; Cristancho, Daniel; Reyes-Esteves, Sahily; Khan, Farhan; Favilla, Christopher G.; Messé, Steven R.; Mullen, Michael T. (Frontiers in Neurology, 2021)
Background and purpose: Dual antiplatelet therapy (DAPT), compared to single antiplatelet therapy (SAPT), lowers the risk of stroke or death early after TIA and minor ischemic stroke. Prior trials excluded moderate to severe strokes, due to a potential increased risk of bleeding. We aimed to compare in-hospital bleeding rates in SAPT and DAPT patients with moderate or severe stroke (defined by NIHSS ≥4). Methods: We performed a retrospective cohort study of ischemic stroke over a 2-year period with admission NIHSS ≥4. The primary outcome was symptomatic intracranial hemorrhage (ICH) with any change in NIHSS. Secondary outcomes included systemic bleeding and major bleeding, a composite of serious systemic bleeding and symptomatic ICH. We performed analyses stratified by stroke severity (NIHSS 4-7 versus 8+) and by preceding use of tPA and/or thrombectomy. Univariate followed by multivariate logistic regression evaluated whether DAPT was independently associated with bleeding. Results: Of 377 patients who met our inclusion criteria, 148 received DAPT (39%). Symptomatic ICH was less common with DAPT compared to SAPT (0.7% vs 6.4%, p<0.01), as was the composite of major bleeding (2.1% vs. 7.6%, p=0.03). Symptomatic ICH was numerically less frequent in the DAPT group, but not statistically significant, when stratified by stroke severity (NIHSS 4-7: 0% vs. 5.9%, p=0.06; NIHSS 8+: 1.5% vs. 6.6%, p=0.18) and by treatment with tPA and/or thrombectomy (Yes: 2.6% vs. 9.1%, p=0.30; No: 0% vs. 2.9%, p=0.25). DAPT was not associated with major bleeding in either the univariate or the multivariate regression. Conclusions: In this single center cohort, symptomatic ICH and the composite of serious systemic bleeding and symptomatic ICH was rare in patients on DAPT. Relative to single antiplatelet therapy DAPT was not associated with an increased risk of in-hospital bleeding in patients with moderate and severe ischemic stroke.